Cáncer de mama y ovario hereditario:consejo genético, seguimiento y reducción del riesgo - Graña, Begoña; Vega, Ana; Cueva, Juan (Psicooncología, 2005)
Of the approximately 16.000 new cases of breast cancer annually diagnosed in Spain, between 5 and 10% are hereditary. A family history of breast cancer is the main criterion to suspect that we could be facing a case of hereditary breast cancer (HBC). Nowadays, mutations in BRCA1 and BRCA2 are the most commonly identified germline alterations associated with HBC. Testing of BRCA1 and BRCA2 in the context of genetic counseling has an important role in risk assessment of breast cancer and associated malignancies, such as ovarian cancer,in carrier individuals. An accurate diagnosis of the hereditary breast and ovarian cancer syndrome (HBOC) is necessary to establish appropriate screening and risk reduction recommendations in the affected individual and at risk relatives.